Associação entre o comprimento do telômero e a ocorrência de quedas em idosos - Dzivielevski, Alessandra Mara Oliveira (2021)
Introduction: Human aging is considered a complex process, which leads to several physiological and systemic changes that favor the occurrence of falls and chronic-degenerative disorders. The fall, in particular, has been considered as one of the most disabling and worrying geriatric syndromes, and, despite being widely studied, it still requires investigation with regard to the biological aspects related to it. In this sense, studies using biomarkers (quantifiable biological parameters), can help to better understand the intrinsic factors related to falls. Among the biomarkers, the telomere length stands out, because it is closely related to gene expression, chromosomal stability and vulnerability to the development of chronic diseases. Objective: To analyze the association between telomere length and the occurrence of falls in the elderly. Method: Sectional study carried out with 448 elderly people. Data collection was carried out in two stages, the first being a personal interview and the second, blood collection. The blood sample was used for the relative quantification of the size of the telomeres by means of qPCR in real time. The dependent variable of the study was the occurrence of a fall in the year prior to the interview. In the data analysis, descriptive statistics and multiple logistic regression were used. Results: The prevalence of the occurrence of at least one fall in the year prior to the interview was 27.90%. Older people with shorter telomere length (OR=1.97; 95%CI=1.01-3.89), female (OR=2.26; 95%CI=1.32-3.86), aged 80 years or more (OR=1.88; 95%CI=1.01-3.56), dependent for basic activities of daily living (OR=2.56; 95%CI=1.38-4.72), and using polypharmacy (OR=1.87; 95%CI=1.20-2.92) were more likely to fall. Conclusions: Shorter telomere length was associated with the occurrence of falls, which demonstrates the relationship of genetic biomarkers in reducing the individual's intrinsic capacity and reinforces the relevance of preventive measures against falls.